Free Vibration Analysis of Functionally Graded Sandwich Plates with a Homogeneous Core - J.R. Cho (Applied Sciences, 2022)
The functionally graded (FG) sandwich plate has attained much attention in recent years due to its potential for exhibiting the merits of sandwich construction and FGM. Accordingly, intensive studies have focused on FG sandwich plates to investigate their mechanical behaviors. However, these mechanical behaviors are still in need of further investigation, particularly with respect to the major parameters. In this context, this paper intends to parametrically investigate the free-vibration behavior of the FG sandwich plate with a homogeneous core by developing a reliable and effective numerical method. This numerical method was based on hierarchical models, developed from the spectral model accuracy, and the 2-D natural element method (NEM). The hierarchical models were derived from the 3-D elasticity and the NEM was characterized by high smooth interpolation functions. From the verification experiments, the proposed method shows a good agreement with the reference and a uniform convergence to the 3-D elasticity. The free vibration characteristics of FG sandwich plates with a homogeneous core were investigated using the proposed numerical method. It was found that the calibrated fundamental frequency was significantly influenced by the type of material composing the core, the volume fraction index, the relative thickness and position of core layer, and the plate aspect ratio.